The role of 18F-FDG PET/MRI in assessing pathological complete response to neoadjuvant chemotherapy in patients with breast cancer: a systematic review and meta-analysis - Milad Ghanikolahloo; Hayder Jasim Taher; Ayoob Dinar Abdullah; Mahsa Asadi Anar; Ali Tayebi; Rahil Rahimi; Faranak Olamaeian; Nima Rahimikashkooli; Nima Kargar (Radiation Oncology)
Abstract Background and aim The present study aimed to evaluate the use of 18F-2-[18F]-fluoro-2-deoxy-d-glucose (FDG) PET/MRI (Positron emission tomography-computed tomography) in predicting the pathological response to neoadjuvant chemotherapy (NAC) in patients with breast cancer (BC) compared to the use of MRI (Magnetic Resonance Imaging) alone. Methods We searched numerous databases, including PubMed, Scopus, Embase, and Science Direct, using curated keywords. The variance of each study was determined using the binomial distribution, and STATA version 14 was used to analyze the data by performing random-effect models. Additionally, we calculated study heterogeneity using the chi-squared test and I2 index and utilized funnel plots and Egger tests to assess publication bias. Results The current investigation analyzed 239 patients from six published studies. The pooled estimated sensitivity and specificity of 18F-FDG PET/MRI was 0.91 (95% CI = 0.90 to 0.92, I2 = 100% and P = 0.000) and 0.62 (95% CI = 0.53 to 0.72, I2 = 99.8% and P = 0.000), respectively. Pooled sensitivity and specificity of MRI were 0.78 (95%CI = 0.59 to 0.96, I2 = 100% and P = 0.000) and 0.56 (95%CI = 0.33 to 0.80, I2 = 99.8% and P = 0.000), respectively. Conclusions Based on our findings, the combined form of 18F-FDG PET/MRI imaging is more sensitive and specific than MRI alone for predicting response to NAC in BC patients.